2016
DOI: 10.1007/s10452-016-9586-z
|View full text |Cite
|
Sign up to set email alerts
|

Do age-related changes in feeding habits of brown trout alter structural properties of food webs?

Abstract: The aim of this study was to quantify changes in food webs based on ontogenetic dietary shifts of a top fish predator (here brown trout Salmo trutta L.). Here, the food web of a river in Central Spain (River Tormes) was studied to test the hypothesis that food web structural properties may change according to age-related changes in feeding habits of brown trout. Thus, the food web was established separately for age-0, age-1 and age-2 brown trout using a forward procedure (individual, modular and river networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…the number of feeding linkages) as different functional groups occupy alternative positions (i.e. alternative stable states) in the food web (Amundsen et al, ; Takimoto, ; Nakazawa, , ; van Leeuwen et al, ; Sánchez‐Hernández, ). However, it may not be possible to identify alternative positions in food webs clearly when predators undergo multiple ODSs (i.e.…”
Section: Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…the number of feeding linkages) as different functional groups occupy alternative positions (i.e. alternative stable states) in the food web (Amundsen et al, ; Takimoto, ; Nakazawa, , ; van Leeuwen et al, ; Sánchez‐Hernández, ). However, it may not be possible to identify alternative positions in food webs clearly when predators undergo multiple ODSs (i.e.…”
Section: Consequencesmentioning
confidence: 99%
“…respiration and primary productivity). Network-based approaches have demonstrated that the functional role of fish is developmental-stage specific (Ramos-Jiliberto et al, 2011;Sánchez-Hernández, 2016). ODSs, therefore, have the potential to have important effects on energy pathways and food-web structure and dynamics (Woodward et al, 2005;Miller & Rudolf, 2011;Nakazawa, 2015).…”
Section: (2) Food Webs and Ecosystem Processesmentioning
confidence: 99%
“…Brown trout is one of the most widespread salmonid fish species in European inland waters and its natural distribution is fundamentally restricted to this area (Elliott, ), although it has been introduced to many countries worldwide (Elliott, ). Moreover, brown trout is of great importance from an ecological and socio‐economic point of view, as it is the top‐predator fish in many river systems (Jensen et al., ; Sánchez‐Hernández, ) and one of the most popular and important sport‐fishing species (Almodovar & Nicola, ). The ecology of brown trout has been studied for many years (Elliott, ; Jonsson & Jonsson, ) and several studies on population dynamics have been conducted in different regions (Bagliniére, Maisse, Lebail, & Nihouarn, ; Elliott, ; Lobón‐Cerviá, ; Mortensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…mortality rates, survival rates) and, therefore, it is very difficult to understand how different population traits interact with river connectivity to generate the observed spatial patterns. In this regard, building population dynamics models of river species at a river network scale is a promising approach to better understand how the effects of altered connectivity might propagate through a river network (Charles, Bravo importance from an ecological and socio-economic point of view, as it is the top-predator fish in many river systems (Jensen et al, 2008;Sánchez-Hernández, 2016) and one of the most popular and important sport-fishing species (Almodovar & Nicola, 1998). The ecology of brown trout has been studied for many years (Elliott, 1994;Jonsson & Jonsson, 2011) and several studies on population dynamics have been conducted in different regions (Bagliniére, Maisse, Lebail, & Nihouarn, 1989;Elliott, 1994;Lobón-Cerviá, 2012;Mortensen, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Except for S. trutta, the Tormes ichthyofauna is composed of endemic species. S. trutta is the main top predator (Sánchez-Hernández, 2016).…”
Section: Methodsmentioning
confidence: 99%